OBITUARY: Professor Harnek Singh Garcha (04.03.1940 - 20.03.2016) - Atri, N S (Mushroom Research, 2019)
Professor Harnek Singh Garcha, a devoted teacher and an accomplished mushroom mycologist, was born on 4th Â March, 1940 at Village Todarpur situated in District Ludhiana. He did his Doctorate with Late Professor K.S.Thind from Punjab University, Chandigarh and subsequently joined as Assistant Mycologist in the Department of Microbiology, College of Basic Sciences and Humanities, Punjab Agricultural University, Ludhiana in 1971 where he rose to the coveted position of Professor and Dean of the college. At this University, besides his normal teaching and research engagements he was also involved in extension education and university administration. For improving his research acumen, he undertook training in solid state fermentation and bioconversion technology at Department of Biology University Science Centre, Chinese University, Shatin, NT, Hong Kong and Bacteriological Research Centre Institute Armand Frappier (IAR) University due Quebec, Laval, Canada. At Punjab Agricultural University Ludhiana, he laid solid foundation for establishment of Mushroom Research Centre. The technology developed by him for the cultivation of edible fungi using agricultural wastes has been included in â€œThe Packages of Practicesâ€. As many as 125 genera of fungi and actinomycetes isolated by him from compost/casing are catalogued with Commonwealth Mycological Institute, England.Â